Cation self-diffusion of 44 Ca, 88 Y, and 96 Zr in single-crystalline calcia- and yttria-doped zirconia - Kilo, M. (2003)
Self-diffusion of calcium, yttrium, and zirconium in single-crystalline yttria-stabilized zirconia (YSZ) and calcia-stabilized zirconia (CSZ) was investigated. The stable isotopes 44 Ca and 96 Zr were used as tracers for zirconium and calcium diffusion. It was observed that in YSZ, zirconium and yttrium bulk diffusivity were maximum for a stabilizer content of 10-11 mol%, and in CSZ both calcium and zirconium tracer diffusion are independent of the calcium content. Results show that the cation diffusion occurs either via free vacancies or via bound vacancies.